“LAS RELACIONES INTERPERSONALES EN EL DESEMPEÑO LABORAL DE LOS FUNCIONARIOS DE LA COOPERATIVA DE AHORRO Y CRÉDITO “PADRE JULIAN LORENTE LTDA.” (MATRIZ) DE LA CIUDAD DE LOJA Y LA INTERVENCIÓN DEL TRABAJADOR SOCIAL” - Maldonado Jaramillo, Karen Janina (2021)
The present investigative work called "Interpersonal relations in the work performance of the officials of the savings and Credit Cooperative" Padre Julian Lorente Ltd. ". (Matrix) of the city of Loja and the intervention of the social worker”, responds to the need to determine how interpersonal relationships affect the work performance of the employees of the Savings and Credit Cooperativa “Padre Julián Lorente Ltda.”. In this sense, the purpose of the investigation is to contribute to the Cooperativa de Ahorro y Crédito "Padre Julián Lorente Ltda." through strategies framed in a proposal, in order to guide and improve the work performance of the cooperative's officials. The specific objectives made possible the scientific argumentation of the object of study, determining and identifying the incidence of interpersonal relationships in the work performance of the Cooperativa de Ahorro y Crédito Padre Julián Lorente Ltda. To validate the knowledge acquired during the research process, the scientific method was used, method inductive-deductive, which allowed to fulfill the objectives set, starting with the scientific support of the categories of analysis, making possible the Justification of the work given that it has theoretical value and social relevance, the methodology used allowed us to make significant findings about the interpersonal relationships existing within the institution. The main findings derived from the analysis of the field work in which surveys were applied to 50 officials of the institution and structured interviews both to the general manager and head of human talent, it is determined that interpersonal relationships are indifferent between the members of the institution, where communication strategies are not shown or established, which generates a conflict in various situations which affects work performance, before this the same officials express the importance and need to implement a social work professional to the work group, for care integral of the same, and for the strengthening of the multidisciplinary team of the company.